THE INFLUENCE OF PARENTAL SUPPORT DIMENSIONS IN SHAPING THE INTENTION TO CONTINUE THE FAMILY BUSINESS DAUGHTER SUCCESSORS WITH SELF-EFFICACY AS A MEDIATOR - Nisa, Puspayani; Padmalia , Metta (FEB Universitas Sam Ratulangi Manado, 2024)
Abstract. The intention to continue the family business can be influenced in particular by parents. This study discusses the influence of parental support dimensions including Instrumental Assistance (IA) and Career-related modeling (CRM) in forming the intention to continue a family business that focuses on female successors with self-efficacy as mediation. Through this research, it is expected to be able to provide the latest views, especially girls, when in the family business. The sampling technique used was a purposive sampling technique on 195 girls aged at least 18 years who had contributed to the family business. This research was tested using SmartPLS 3.0 and JASP software. Through this study, the findings of this study indicate that both Instrumental Assistance (IA) and self-efficacy play significant roles in shaping a daughter's inclination to achieve success within the context of a family business. Unlike the previous Career-Related Modeling (CRM) based on specific studies indicate that self-efficacy does not serve as a mediating factor in the relationship between Career-Related Modelling and a daughter's intention to succeed in the family business. Abstrak. Tujuan untuk melanjutkan bisnis keluarga dapat dipengaruhi khususnya oleh orang tua. Penelitian ini membahas tentang pengaruh dimensi dukungan orang tua meliputi Instrumental Assistance (IA) dan Career-related modeling (CRM) dalam membentuk niat untuk melanjutkan bisnis keluarga yang fokus pada penerus perempuan dengan efikasi diri sebagai mediasinya. Melalui penelitian ini diharapkan mampu memberikan pandangan terkini khususnya anak perempuan ketika terjun dalam bisnis keluarga. Teknik pengambilan sampel yang digunakan adalah teknik purposive sampling terhadap 195 anak perempuan berusia minimal 18 tahun yang pernah berkontribusi pada bisnis keluarga. Penelitian ini diuji dengan menggunakan software SmartPLS 3.0 dan JASP. Melalui penelitian ini, temuan penelitian ini menunjukkan bahwa baik Instrumental Assistance (IA) maupun self-efisiensi berperan penting dalam membentuk kecenderungan anak perempuan untuk mencapai kesuksesan dalam konteks bisnis keluarga. Berbeda dengan Career-Related Modeling (CRM) sebelumnya, berdasarkan penelitian tertentu menunjukkan bahwa self- efikasi tidak menjadi faktor mediasi dalam hubungan antara Career-Related Modeling dan niat anak perempuan untuk sukses dalam bisnis keluarga